Effects of Scratch Gamification with MDA on Students’ Engagement and Learning Outcomes - Agustinus Sembiring; Heni Jusuf; Handri Santoso (Formosa Journal of Computer and Information Science, 2026)
This study aims to examine the effect of Scratch-based gamification using the MDA (Mechanics–Dynamics–Aesthetics) model on students’ engagement and learning outcomes in primary education. A quasi-experimental method with a pretest–posttest design was applied to 115 students. Data were collected through tests and questionnaires and analyzed using paired sample t-tests and descriptive analysis. The results showed a significant improvement in learning outcomes, with a mean pretest score of 56.84 and posttest score of 71.03 (t = -26.57; p < 0.001). In addition, students’ engagement was categorized as high (mean = 3.73). These findings indicate that Scratch-based gamification integrated with the MDA model is effective in improving learning quality.